2020
DOI: 10.1113/ep088486
|View full text |Cite
|
Sign up to set email alerts
|

The sweat glands’ maximum ion reabsorption rates following heat acclimation in healthy older adults

Abstract: We examined whether the eccrine sweat glands' ion reabsorption rates improved following heat acclimation (HA) in older individuals. Ten healthy older adults (>65 years) completed a controlled hyperthermic (+0.9 • C rectal temperature, T re) HA protocol for nine non-consecutive days. Participants completed a passive heat stress test (lower leg 42 • C water submersion) pre-HA and post-HA to assess physiological regulation of sweat gland ion reabsorption at the chest, forearm and thigh. The maximum ion reabsorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 53 publications
(116 reference statements)
0
15
0
Order By: Relevance
“…It would also appear that peripheral adaptations to the sweat gland are limited in older individuals undertaking exercise HA (targeting a + 0.9°C increase in core temperature) for nine days. 15 That study reported sudomotor responses to iontophoresis during passive heating as unchanged after HA, and whilst maximal ion absorption improved, this decayed within seven days. 15 The success of the longer duration protocols i.e.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“…It would also appear that peripheral adaptations to the sweat gland are limited in older individuals undertaking exercise HA (targeting a + 0.9°C increase in core temperature) for nine days. 15 That study reported sudomotor responses to iontophoresis during passive heating as unchanged after HA, and whilst maximal ion absorption improved, this decayed within seven days. 15 The success of the longer duration protocols i.e.…”
Section: Introductionmentioning
confidence: 91%
“…15 That study reported sudomotor responses to iontophoresis during passive heating as unchanged after HA, and whilst maximal ion absorption improved, this decayed within seven days. 15 The success of the longer duration protocols i.e. six to nine sessions [12][13][14][15] , over shorter protocols i.e.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Five papers deal with this area and investigate the impact of passive acclimation on kidney function in the heat (Ravanelli, Barry, Schlader, & Gagnon, 2021a); the impact of 5 weeks of heat training on haemoglobin mass in elite cyclists (Rønnestad et al., 2021); the relative roles of heat acclimation and increases in fitness in exercise training‐induced thermoregulatory adaptations (Ravanelli, Gagnon, Imbeault, & Jay, 2021b); changes in aerobic capacity, heat shock protein 72, markers of mitochondrial biogenesis and oxidative phosphorylation in skeletal muscle with heat acclimation and low intensity exercise (Mang et al. 2021); and the induction and decay of sweat gland maximum ion reabsorption rates following heat acclimation in healthy older adults (Gerrett, Amano, Inoue, & Kondo, 2021).…”
mentioning
confidence: 99%